Redescription of Mugil setosus Gilbert 1892 with comments on the occurrence of Mugil curema Valenciennes 1836 in the Pacific Ocean (Teleostei: Perciformes: Mugilidae) - Britzke, Ricardo; Menezes, Naércio A.; Nirchio, Mauro (Zootaxa, 2019)
Mugil setosus Gilbert 1892 was originally described by Gilbert based on specimens from Clarion Island, in the western and most remote of the Revillagigedo Islands, about 1,000 km off the western Pacific coast of Mexico. Examination of the type of material and recently collected specimens from Ecuador and Peru, resulted in the redescription provided herein. Diagnostic characters of the species were mainly: tip of the pelvic fin reaching beyond the vertical through the base of the third dorsal-fin spine, the pectoral-fin rays with ii+13–14 rays, the anterodorsal tip of second (soft) dorsal fin uniformly dark, and an external row of larger teeth, and more internally a patch of scattered smaller teeth, visible mainly in adults 150 mm SL. The expansion of geographic distribution of Mugil setosus and occurrence of Mugil curema Valenciennes 1836 in the Pacific Ocean are discussed.